Pilot Study to Evaluate Performance of Frost-Yuzu Fruit Trees under Protected Cultivation - Byeong-Sam Kim; Bo-Bae Lee; Seok-Kyu Jung; Hyun-Sug Choi (Agriculture, 2021)
This study was initiated to observe the performance of yuzu (Citrusjunos Sieb. ex Tanaka) fruit trees when affected by a late freezing in 2018 and to evaluate the recovery of frost-damaged trees during post management under protected cultivation. A—4.9 °C of minimum daily temperature and 40-day drought occurred during dormancy, which then received heavy precipitation between early- and mid-March, with 15 m s−1 more than maximum instantaneous wind speeds frequently observed. This resulted in observed decreases in height, width and volume as well as in fruiting, fruit weight and yield, as well as yield index in 60–90% defoliated yuzu trees, in addition to higher rates of shoot dieback compared to trees that experienced only 0–30% defoliation. Lower performance and recovery rates of trees grown on flat land compared to trees on sloped land were also observed. Tree and net windbreaks did not significantly affect tree vegetative growth and fruit productivity but were found to have lowered shoot mortality in 2018 and 2019. Mulch with an irrigation after freezing or foliar urea application was shown to effectively increase vegetative tree growth and fruit productivity and reduce shoot mortality.